Impact of storage conditions on seed germination and seedling growth of wild oat (Avena fatua L.) at different temperatures - Sarić-Krsmanović, Marija M; Gajić Umiljendić, Jelena; Šantrić, Ljiljana; Radivojević, Ljiljana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2016)
The influence of seed storage conditions and different temperatures (5˚C, 10˚C,15˚C, 20˚C, 25˚C, 30˚C and 26˚C/21˚C) during germination and seedling development on seed germination, shoot length and germination rate of wild oat (Avena fatua L.) was examined. Germinated seeds were counted daily over a period of ten days and shoot length was measured on the last day, while germination rates were calculated from those measurements. The results showed that seed storage under controlled conditions (T1: temperature 24±1°C, humidity 40-50%; T2: temperature 26±1°C, humidity 70-80% and T3: temperature 4˚C) for periods of 3 (t1) and 12 (t2) months had a significant influence on germination of wild oat seeds. The percentage of germinated seeds under all examined temperatures was higher when they were stored for 12 months under controlled temperature and humidity. The results also showed that temperature had a significant effect on the percentage of germination and germination rate of A. fatua seeds. The highest total germination occurred at 15˚C temperature (T1: t1 - 41.25%, t2 - 44.37%; T2: t1 - 28.13%, t2 - 34.37%; T3: t1 - 10.63%, t2 - 12.50%). Germination percentage under an alternating day/night photoperiod at 26˚C/21˚C temperature was higher in all treatment variants (T1: t1 - 8.13%, t2 - 10.00%; T2: t1 - 11.87%, t2 - 13.13%; T3: t1 - 2.42%, t2 - 2.70%) than germination in the dark at 25˚C, 30˚C and 5˚C.
Keywords: Germination; Seed storage; Temperature; Wild oat